DAKWAH STRUKTURAL PAKAIAN MUSLIMAH DI KELANTAN - MALAYSIA - Rasyidah Rasyidah (Takammul : Jurnal Studi Gender dan Islam Serta Perlindungan Anak, 2017)
Structural da'wah strategy about moslemah dress often cause discourse in the context of state authority, freedom of religion and women’s control to their bodies. Furthermore it is considered as politicization of women’s body in the name of religion. So some areas that implement da'wah like this, get resistance from women as mad‘u. Interestingly, Kelantan that implemented the same strategy, did not get this resistance. This is a feature that needs to be studied, especially about the strategies implemented. The results of the study show that there are six strategies: creative media campaign, clothing regulation in trade, supervision & counseling, formal education, non formal and habituation in the community, enliven the philosophy of aurat through culture, as well as the establishment of uniform standards. These six strategies are developed through the role models of da'i, gentle attitudes, giving a balance between appreciation and sanctions, and building understanding of the meaning of muslimah clothing among individuals, families and communities. This is what causes the structural da'wah strategy about moslemah dress not getting a meaningful resistance in Kelantan.